A new DBS card with spot sizes independent of the hematocrit value of blood. (September 2015) - Mengerink, Ynze; Mommers, John; Qiu, Jun; Mengerink, Josh; Steijger, Odile; Honing, Maarten
Background: DBS cards have been a big promise for decades. However, blood with low hematocrit (Ht) values results on regular cellulose-based DBS cards in larger spot sizes, compared with blood with high Ht-values. A new material has been developed to solve this problem.Results: This material, based on hydrophilic-coated woven polyester fibers, shows spot sizes independent of the Ht-value of blood. Homogeneity over the spot is within 10% RSD.Conclusion: Quantitative measurements over a broad Ht range show nonbiased results compared with whole spot analysis. The cards are experienced as reproducible, robust and easy to use on aspects of punchability and extractability.